Alexithymia and cortisol awakening response in people with eating disorders. (13th April 2021) - Cascino, G.; Monteleone, A.M.; Marciello, F.; Ruzzi, V.; Pellegrino, F.; Monteleone, P.
Abstract : Introduction: Alexithymia, that is the inability to recognize and describe one's own emotions, is a transdiagnostic feature across eating disorders (EDs) and it has been associated to a prolonged stress exposure. Objectives: Therefore, we evaluated whether alexithymia affects the hypothalamus-pituitary-adrenal (HPA) axis functioning in patients with anorexia nervosa (AN) or bulimia nervosa (BN). Methods: Twenty-six women with AN and 26 with BN participated in the study. Alexithymia was evaluated by the Toronto Alexithymia Scale–20 and eating-related psychopathology was measured by the Eating Disorder Inventory-2. The activity of the HPA axis was assessed by the salivary cortisol awakening response (CAR). Group differences in saliva CAR were tested by repeated measures 3-way ANOVA with diagnosis and alexithymia as between-subject factors. Results: The prevalence of alexithymia did not differ significantly between the two diagnostic groups (c 2 =1.24, p=0.26). Alexithymia was associated with more severe eating-related psychopathology in AN women but not in BN women. A significant reduction in the magnitude of CAR occurred in alexithymic patients with BN compared to non-alexithymic patients with BN (t = 3.39, p = 0.008), but not in alexithymic women with AN (t = 0.67, p = 0.54). Conclusions: These results confirm the presence of a more severe eating-related psychopathology in alexithymic individuals with AN and show, for the first time, an association between alexithymia and a dampened basal activity of the HPA axis in BN. Disclosure: No significant relationships.